Characterisation of Stress Intensity Factor with Magnetic Flux Signal Leakage in Stable Fatigue Crack Growth Region S. R. Ahmad ...[et al.] - Ahmad, S. R.; Arifin, A.; Abdullah, S.; M. Yunoh, M. F. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper presents the characterisation of the stress intensity factor range ΔK, with the magnetic flux gradient, dH(y)/dx signals obtained using the metal magnetic memory (MMM) method during fatigue crack growth test. The MMM method is a passive non-destructive testing technique developed for the examination of self-magnetic leakage field signals which were generated in the stress concentration zones. In this paper, the fatigue crack growth test was conducted by applying a constant amplitude loading at different stress ratios. The scanning device and crack opening displacement gauges were used for acquiring the magnetic signals and crack growth parameter, respectively. The relationship between the dH(y)/dx signals, fatigue crack growth rate, da/dN and ΔK was determined. As a result, some similarities were observed between the ΔK and dH(y)/dx signals; wherein both were seen to increase with an increase in the value of da/dN. Furthermore, the analysis of the relationship between dH(y)/dx and ΔK focused on the stable crack growth region and noted that the correlation of determination ranged between 0.9286 - 0.9788. This indicates that dH(y)/dx signals can be used to evaluate the fatigue crack growth of the material.